MSCI Downgrade to Frontier Market: Lessons for Indonesia from Three Countries - Muhammad Ananda Fakhri; Farianita Lestari; Berry Dhiyashavana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study investigates the impact of MSCI reclassification from Emerging Market (EM) to Frontier Market (FM) on stock market return and capital flow dynamics, using a comparative approach across three historical cases: Jordan (November 2008), Argentina (May 2009), and Morocco (November 2013). The research employs two complementary methods: (1) an event study using daily stock index data from Investing.com, measuring cumulative abnormal returns (CAR) via the Market Model with MSCI World Index as benchmark, tested using the Brown-Warner BMP test; and (2) a before-after analysis using annual Balance of Payments data from the World Bank (indicator BN.KLT.PTXL.CD), tested using the Wilcoxon Signed-Rank Test. All statistical analyses were performed using RStudio 2024.09.2+398. Results show that Jordan experienced the most severe impact with CAR reaching -54.43% (p<0.01) at ED [-20,+60] and -71.35% (p<0.01) at ED [-60,+120], confirming the Price Pressure Hypothesis. Morocco exhibited limited short-term price impact due to an FM premium effect, but recorded a net foreign flow decline of USD -1.554 billion post-downgrade. Argentina showed anomalous positive CAR attributed to Global Financial Crisis recovery effects coinciding with the downgrade period. These findings serve as empirical benchmarks for Indonesia, which faces a MSCI rebalancing freeze since January 2026 and potential downgrade risk ahead of the May 2026 review.